Formulation Design and Functional Characterization of a Novel Fermented Beverage with Antioxidant, Anti-Inflammatory and Antibacterial Properties - Ameni Abdi; Emna Gatri; Pasquale Filannino; Sana M’Hir; Lamia Ayed (Beverages)
The aim of this study was to use different concentrations of lemon juice and honey to improve the formulation of a green tea water kefir (GTWK) beverage by applying a central composite design (CCD). Honey’s concentration was 10–50% and lemon juice concentration was 1–5%, these were used as the independent factors, whereas pH, bacteria and yeasts’ count, total phenolic content, % DPPH. scavenging activity, and overall acceptability were used as the dependent factors. The optimal concentration of honey and lemon juice for highest microbial count, antioxidant activities and overall acceptability was 42.85% and 1.771%, respectively. The analysis of variance revealed that the model was well-fitting, with R2 ranging from 87.27% to 96.95%, adj-R2 ranging from 78.17% to 94.26% and a non-significant lack of fits. The optimized fermented beverage showed antibacterial potential against Echerichia coli ATCC11229, Staphylococcus aureus ATCC6538 and Salmonella typhimirium ATCC14028 strains. The anti-inflammatory activity was evaluated on CaCo-2 and RAW 264.7 cells. According to ELISA assay, a significant decrease (p < 0.05) in TNF-α concentration was found after inflammatory stimulation, from 1205.41 ± 55.87 pg/mL to 478.17 ± 69.12 pg/mL.